2010
DOI: 10.1007/s00421-010-1668-3
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of plasma adrenomedullin by epinephrine infusion during head up tilt

Abstract: We investigated whether head up tilt (HUT) with and without simultaneous epinephrine infusion modulate plasma adrenomedullin. We studied eight healthy male volunteers, using two 5 min 70° HUT trials: control (saline infusion) and intervention (epinephrine infusion, titrated to a dose which increased supine systolic pressure by 20% above resting values). Protocols were randomized and separated by 2 weeks. Cardiac function and systolic time intervals, recorded using a phonocardiograph microphone, included left v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
0
10
2
Order By: Relevance
“…This is in contrast to our previous findings [4,21] in which significant rises in adrenomedullin levels were demonstrated using only HUT to simulate orthostatic challenge. This is in contrast to our previous findings [4,21] in which significant rises in adrenomedullin levels were demonstrated using only HUT to simulate orthostatic challenge.…”
Section: Adrenomedullin Responsecontrasting
confidence: 99%
“…This is in contrast to our previous findings [4,21] in which significant rises in adrenomedullin levels were demonstrated using only HUT to simulate orthostatic challenge. This is in contrast to our previous findings [4,21] in which significant rises in adrenomedullin levels were demonstrated using only HUT to simulate orthostatic challenge.…”
Section: Adrenomedullin Responsecontrasting
confidence: 99%
“…Rat studies showed that NA increases ADM production and secretion from endothelial cells by stimulation of protein kinase C through the alpha-1 receptors and cAMP through beta receptors (Isumi et al, 1998). In a study conducted by Roessler et al (2011) a marked increase in plasma ADM concentration was observed after A infusion during head up tilt in humans. However, we found no significant correlation between plasma A and ADM levels.…”
Section: Discussionmentioning
confidence: 97%
“…6 In addition, the activated platelets release 5-hydroxytryptamine and the expression of cyclooxygenase-2 is induced, enhancing the contractile response and the development of intracellular acidosis which increases the concentration of inorganic phosphate, pyruvate, hydrogen ions, and lactate. 4 Furthermore, the ROS-mediated damage of the fatty acids of membrane phospholipids increases cell membrane permeability, diminishing the concentration of intracellular K + and Mg 2+ and increases that of Na + and Ca 2+ which together with the depletion of adenosine triphosphate (ATP) and the increased oxidative stress form the mitochondrial permeability transition pore (MTP). 4,7 Of note, the mitochondrial metabolism is impaired and free fatty acids, long-chain acyl CoA, and acylcarnitine accumulate and are incorporated into membranes impairing their function.…”
Section: Cardiac Arrest -The Onset Of the Ischemic Cascadementioning
confidence: 99%
“…Interestingly, the adrenal blood flow further worsens due to microvessel contraction, a phenomenon which is partly mediated by adrenomedullin. 4 At the same time, various cytokines, complement components, and other molecules are synthesized and released in response to global hypoxia, such as tumor necrosis factor-a (TNF-a), interleukin 1b (IL-1b), C3, C4, C5, C5b-9, P-selectin, and intercellular adhesion molecule-1, and reactive oxygen species (ROS) are released from activated polymorphonuclear leukocytes (PMN). 3 The cellular response to hypoxia is coordinated by the hypoxia-inducible factor (HIF) and its regulator, the Von Hippel-Lindau tumor suppressor protein.…”
Section: Cardiac Arrest -The Onset Of the Ischemic Cascadementioning
confidence: 99%